Сharacterization of the probiotic potential of Lacticaseibacillus paracasei 2 LB strain - Abitayeva, Gulayim; Kurmangali, Diana; Baikonys, Temirlan; Bekshin, Zhandarbek (Eurasian Journal of Applied Biotechnology, 2025)
Background: To develop effective probiotics, it is necessary to considering the strain-specific characteristics, which requires detailed genomic and phenotypic studies to understand the functional probiotic mechanisms (Wang J., 2022). The aim of this study is characterization of a probiotic strain Lacticaseibacillus paracasei 2 LB. Materials and methods: The potential of the probiotic 2 LB strain from koumiss were studied using a combination of in vitro assays and WGS genome analysis (Kandasamy S., 2024). Results: In vitro evaluation demonstrated that 2 LB strain was well tolerated in a simulated gastrointestinal environment, grew well at pH = 3.5, 0.3% bile salts and 2-8% NaCl. Analysis of antimicrobial activity by agar diffusion method showed that the 2 LB can effectively inhibit the growth of pathogens Escherichia coli, Salmonella typhimurium, Staphylococcus aureus. The 2 LB strain had high rates of adhesive properties auto-aggregation and co-aggregation to pathogens. A comparative genomic analysis of the core and pan-genome of 2 LB strain was performed. In the 2 LB strain genome, with a size of 3,066,038 nucleotide pairs and a GC content of 46.25%, 2,932 coding DNA sequences (CDS), 6 genes for ribosomal RNA, and 59 genes for transfer RNA were found. In terms of the stability of its genetic material, the absence of the ability to synthesize virulence factors and genes responsible for antibiotic resistance were characterized. Conclusion: The results indicate that the 2 LB strain has potential for probiotic development. WGS genome analysis of the 2 LB strain will be further explored. Acknowledgement: This research was funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (grant number AP 19679863). Key words: Lacticaseibacillus paracasei, koumiss, probiotic, sequencing References: Wang, J., Wang, T., Li, Y. et al. Comparative genomic analysis of Lacticaseibacillus paracasei SMN-LBK from koumiss. Front. Microbiol 13, 1042117(2022). Kandasamy, S., Lee, K.-H., Yoo, J. et al. Whole genome sequencing of Lacticaseibacillus casei KACC92338 strain with strong antioxidant activity, reveals genes and gene clusters of probiotic and antimicrobial potential. Front. Microbiol 15, 1458221 (2024).